2020
DOI: 10.1177/1460458219895434
|View full text |Cite
|
Sign up to set email alerts
|

Risks and medication errors analysis to evaluate the impact of a chemotherapy compounding workflow management system on cancer patients’ safety

Abstract: A failure modes, effects and criticality analysis was supported by an observational medication error rate study to analyze the impact of Phocus Rx®, a new image-based workflow software system, on chemotherapy compounding error rates. Residual risks that should be a target for additional action were identified and prioritized and pharmacy staff satisfaction with the new system was evaluated. In total, 16 potential failure modes were recognized in the pre-implementation phase and 21 after Phocus Rx® implementati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…14 Similarly, in a study assessing chemotherapeutic comparative risk analysis before and after implementation of a remote verification system, the relative risk reduction of compounding error rate was 63% after implementing a workflow system. 16 In this retrospective observational study, use of a remote verification system showed variation between workflow stations and lack of standardization across delivered chemotherapeutics to patients. Image analyses demonstrated that the highest number of orders with a deviation from best practice were those that exceeded the ISMP >10% additive volume guideline.…”
Section: Discussionmentioning
confidence: 83%
“…14 Similarly, in a study assessing chemotherapeutic comparative risk analysis before and after implementation of a remote verification system, the relative risk reduction of compounding error rate was 63% after implementing a workflow system. 16 In this retrospective observational study, use of a remote verification system showed variation between workflow stations and lack of standardization across delivered chemotherapeutics to patients. Image analyses demonstrated that the highest number of orders with a deviation from best practice were those that exceeded the ISMP >10% additive volume guideline.…”
Section: Discussionmentioning
confidence: 83%
“…Positive results have been seen from digital image-based workflow systems. Such systems enable repetitive processes, such as medication preparation, to be automated (Marzal-Alfaro et al, 2020). One study investigated the impact of an image-based workflow system, which aimed to reduce risk in the medication process of chemotherapy by digitally guiding technicians through the compounding process.…”
Section: Using His and Big Data To Learn Understand And Inform Decision-makingmentioning
confidence: 99%
“…One study investigated the impact of an image-based workflow system, which aimed to reduce risk in the medication process of chemotherapy by digitally guiding technicians through the compounding process. The authors found the system to be clearly effective in increasing safety (Marzal-Alfaro et al, 2020). In areas such as cancer detection, AI and digital-based image data are also now a common feature.…”
Section: Using His and Big Data To Learn Understand And Inform Decision-makingmentioning
confidence: 99%
“…These errors occur in all cancer treatment plans and may happen in all phases of the chemotherapy process, including prescription, preparation, and administration. They include all types of medication errors, such as wrong patient treatment, administration of wrong regimen, drug, or drug dose, wrong route of administration, errors related to schedules or infusion, and compounding errors (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…While the chemotherapy administration phase is complex and requires many different safety checkpoints to prevent errors, according to the literature, the highest rate of medication errors is related to the prescription phase, with almost 33% of all errors categorized as fatal or lifethreatening for cancer patients (9). The chemotherapy preparation phase is usually considered a critical step; however, the risks and errors remain uncertain, because there are no studies specifically designed to detect these errors (8). Other issues of concern that may compromise the safety and quality of the chemotherapy process include long patient waiting time for chemotherapy due to uncertainties in the chemotherapy workflow and appointment schedules; poor communication and coordination between different care providers (e.g., oncologists, nurses, and pharmacists); and inconsistency in the paper-based documentation of prescriptions and administration information, making it difficult to find previous prescriptions and keep track of the chemotherapy cycle (3,4,(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%